2012
DOI: 10.4093/dmj.2012.36.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Visceral Adiposity on Cardiovascular Autonomic Neuropathy in Patients with Type 2 Diabetes Mellitus

Abstract: BackgroundThe aim of this study was to investigate the influences of visceral adiposity on cardiovascular autonomic neuropathy (CAN) in patients with type 2 diabetes mellitus.MethodsTwo hundred eleven patients with type 2 diabetes participated in this study. Anthropometric and metabolic parameters were measured, and the visceral fat area was assessed using computed tomography. CAN was diagnosed using a cardiovascular reflex test. We analyzed the correlation between the visceral fat area and each parameter in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…In particular, VAT confers risks of metabolic and CV complications [4,24,25]. The possibility of an active metabolic role for VAT in the etiology of MS and CVD may be explained by the fact that the VAT has higher lipolytic activity and directly releases free fatty acids into the portal circulation, and this considerably contributes to insulin resistance [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, VAT confers risks of metabolic and CV complications [4,24,25]. The possibility of an active metabolic role for VAT in the etiology of MS and CVD may be explained by the fact that the VAT has higher lipolytic activity and directly releases free fatty acids into the portal circulation, and this considerably contributes to insulin resistance [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that regional adiposity of the body is more closely associated with atherosclerosis than the magnitude of generalized obesity [ 1 , 3 , 23 ]. In particular, VAT confers risks of metabolic and CV complications [ 4 , 24 , 25 ]. The possibility of an active metabolic role for VAT in the etiology of MS and CVD may be explained by the fact that the VAT has higher lipolytic activity and directly releases free fatty acids into the portal circulation, and this considerably contributes to insulin resistance [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…La neuropatía autonómica cardiovascular (NAC) es la forma clínica más estudiada de las neuropatías autonómicas y diversos trabajos han demostrado su relación con la isquemia miocárdica silente e incluso un aumento de cuatro veces en el riesgo de mortalidad cardiovascular. A su vez la obesidad visceral ha sido mencionada en distintos trabajos con una marcada correlación con alteraciones propias de la disautonomía cardiovascular 3 .…”
Section: Síndrome Metabólico: Intervenciones En El Estilo De Vidaunclassified
“…La obesidad se ha asociado en modelos animales a NAC y en humanos con aumento de la actividad simpática y con efecto inverso sobre la actividad parasimpática 3 .…”
Section: Síndrome Metabólico: Intervenciones En El Estilo De Vidaunclassified
“…Autonomic nerve fibers are prone to damage depending on their location and length. This damage is a subtype of diabetic neuropathy, which can also occur in adipose tissue in relation with autonomic neuropathy or peripheral neuropathy [ 2 3 ], similar to enteric organs in the human body. In obese patients, visceral WAT is associated with increased risk of type 2 diabetes mellitus; however, some patients exhibit decreased fat mass as diabetes progresses although cardiac autonomic neuropathy can be associated with higher waist circumference [ 4 ].…”
Section: Introductionmentioning
confidence: 99%